ORGANIZATIONAL AND LEGAL BASIS OF FUNCTIONING OF THE SCIENTIFIC AND EDUCATIONAL AREA IN UKRAINE UNDER THE CONDITIONS OF THE COVID-19 PANDEMIC - Головко, Світлана Григорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to analyze the regulatory and legal support for the functioning of the domestic scientific and educational sector in the conditions of quarantine restrictions caused by the COVID-19 pandemic. Methods: the main challenges faced by the domestic education system in the context of global changes caused by the coronavirus pandemic as well as foreign experience in overcoming them were highlighted by applying the method of comparative analysis; the system of normative-legal maintenance of functioning of domestic scientific and educational branch in the conditions of quarantine restrictions, the basic directions in its perfection is considered by applying the method of synthesis. Results: trends of education modernization in the conditions of quarantine restrictions are covered; it was found that one of the key trends in this context is the introduction of distance learning technologies and research organization; it is shown that one of the urgent problems both on a national and global scale is the insufficient development of the legal framework for the functioning of the scientific and educational sector and the interaction of its subjects during quarantine; the basic legislation of Ukraine on education-scientific and scientific-technical activities (laws «On Education», «On Higher Education», «On Complete General Secondary Education», «On Scientific and Scientific-Technical Activity») was analyzed and its potential to ensure opportunities for the formation of effective tools for organizing the educational and research process during quarantine restrictions was substantiated; normative-legal acts on realization of educational process, improvement of procedures for the attestation of students of different levels and scientific-pedagogical workers of higher qualification by means of distance learning technologies (in particular, Resolutions of the Cabinet of Ministers of Ukraine, orders and instructions of MES of Ukraine on organization of the work of educational institutions and scientific institutions under quarantine conditions, a new edition of the Regulations on distance learning of comprehensive secondary education, etc.) were covered and the range of organizational and legal issues that need to be standardized was outlined; the ways of the further development of organizational and legal support for the functioning of the domestic scientific and educational sector in quarantine were determined. Discussion: prospects for the widespread introduction of distance technologies in the domestic scientific and educational area using foreign experience and taking into account trends in its organizational and legal support.